AB0599 The oa trial bank: individual patient data meta-analysis of trials investigating the effectiveness of intra-articular corticosteroid injections in patients with knee or hip oa. (23rd January 2014) - Van Middelkoop, M.; Dziedzic, K.; Doherty, M.; Zhang, W.; Bijlsma, J. W.; McAlindon, T.; Lohmander, S.; Bierma-Zeinstra, S. M.
Abstract : Background: Based on small to moderate effect size of the wide range of symptomatic treatments in osteoarthritis (OA), and the heterogeneity of OA patients, treatment guidelines for OA have stressed the need for research on clinical predictors of response to different treatments. A meta-analysis to quantify the effect modified by the predictors using Individual Patient Data (IPD) is suggested. The initiative to collect and analyse IPD in OA research is commenced by the 'OA Trial Bank'. Objectives: The general purpose of this initiative is to reach consensus on the rules for cooperation in a consortium and to develop the methodological issues of meta-analysis with IPD. The first meta-analysis will evaluate the efficacy of intra-articular (IA) corticosteroids for knee or hip OA in specific subgroups of patients with severe pain and (mild) inflammatory signs, over both short and long term follow-up, using IPD from existing trials. Methods: The OA Trial Bank is set-up as a worldwide collaboration that initiates meta-analyses on predefined subgroups of OA patients from existing literature. Internationally acknowledged clinical and epidemiological researchers in the OA field will be approached to formalize the steering committee. A licence agreement will be developed to guarantee legal issues between the OA Trial Bank and data-delivers. For the first IPD analysis, randomised controlled trials (RCTs) evaluating one or more IA corticosteroid preparations in patients with knee or hip OA, published from 1995 up to June 2012, are selected from the existing literature. Corresponding authors of eligible trials will be approached and asked to cooperate in this project. Data obtained from original databases include patient-, disease- and study characteristics and outcome measures. To assess potential subgroup effects, a random-effects model will be used to calculate interaction effects. Results: A chairman, steering committee and an executive coordinator formalize the OA Trial Bank. The steering committee guarantees continuity of the OA Trial Bank and supervises the executive coordinator. The committee has approved and agreed the organisational structure and the tasks of the parties involved (Figure 1). The content of the license agreement was provided by the committee, including data access and transfer, predefined analyses, confidentiality and reliability statement, authorship. A total of 44 publications were selected as potentially eligible. Currently, authors are contacted with a data-delivery request. Conclusions: The international character of the steering committee, the multidisciplinary structure, the patient involvement and the endorsement of the OARSI and EULAR will all strengthen this initiative and hopefully inspire data-delivers, to join this initiative. Disclosure of Interest: None Declared